Cation-oxygen interaction and oxygen stability in CaCu3Ti4O12 and CdCu3Ti4O12 lattices - Matos, M.; Walmsley, L. (Iop Publishing Ltd, 2006)
The cubic perovskite related material CaCu3Ti4O12 has attracted a great deal of attention due to the high values of the static dielectric constant, of order 104, approximately constant in the temperature range 100-600 K. The substitution of Ca by Cd results in a similar temperature dependence but a static dielectric constant more than one order of magnitude lower. A theoretical electronic structure study is performed on CaCu3Ti4O12 (CCTO) and CdCu3Ti4O12 (CdCTO) using a tight binding with overlap method. Although the calculations are performed in a paramagnetic configuration, excellent agreement with experiment was found for the calculated band gap of CCTO. In spite of the fact that the band structures of both systems look practically the same, a significant difference is found in the calculated bond strength of Ca-O and Cd-O pairs, driven by the presence of Ti, with Ca-O interaction in CCTO loosened with respect to Cd-O interaction in the cadmium compound. It is suggested that O vacancies are more easily formed in CCTO, this being related to the lower electronegativity of Ca as compared to Cd. The formation of oxygen vacancies could be the origin of the difference in the static dielectric constant of the two compounds.